IMF Staff papers, Volume 43 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1996)
This paper extends a standard growth model and obtains consistent panel data estimates of the growth retarding effects of military spending via its adverse impact on capital formation and resource allocation. Simulation experiments suggest that a substantial long-term 'peace dividend'-in the form of higher capacity output-may result from markedly lower military expenditure levels achieved in most regions during the late 1980s, and the further military spending cuts that would be possible if global peace could be secured.